EFFECT OF AUDIT FIRM CHARACTERISTICS ON FINANCIAL REPORTING QUALITY OF DEPOSIT MONEY BANKS QUOTED IN THE NIGERIAN STOCK - Akombende, Udie Jacob; Chukwu, U.C. (EBSU Journal of Social Sciences and Humanities, 2024)
The broad objective of the study is to investigate the effect of audit characteristics on financial reporting quality of listed deposit money banks in Nigeria. The specific objectives of the study, were to determine the effect of audit fee, audit firm size and effect of audit tenure on financial reporting quality of listed deposit money banks in Nigeria. The data for the study was collected from four (4) sampled deposit money banks for the period 1999 to 2021. These data were analyzed using descriptive statistics. Linear multiple regression anchored on ordinary least square (OLS) method was employed to test the hypotheses at 5% level of significance. Results from the test revealed that audit fee and audit tenure have negative and significant effect on financial reporting quality; while audit firm size showed positive and significant effect on financial reporting quality of listed deposit money banks in Nigeria. The implication of these findings is that enhancement in the financial reporting quality of the listed banks can be achieved if adequate audit fee and proper audit tenure are maintained between the auditors and the listed banks. The study therefore recommended that big audit firms, adequate audit tenure and audit fees should be encouraged to improved financial reporting quality of the banks.